Analisis Tematik Ayat-Ayat Taskhīr dan Batas Etis Pemanfaatan Alam Perspektif Maqāṣid - Muhammad Aminullah (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2026)
The global environmental crisis calls for a stronger ethical framework in governing the use of natural resources. This study examines the concept of taskhīr in the Qur’an through a thematic approach and formulates ethical limits for the use of nature from the perspective of maqāṣid al-syarī‘ah. Using the method of tafsīr mawḍū'ī, the study analyzes eighteen Qur’anic verses containing derivatives of the word sakhkhara. The findings show that the verses of taskhīr can be classified into three categories: the subjugation of cosmic phenomena, the subjugation of ecological elements and natural resources, and the subjugation granted specifically to certain prophets. The thematic analysis reveals four key messages concerning the relationship between humans and nature. By integrating these findings with the framework of maqāṣid al-syarī‘ah, particularly hifẓ al-bī’ah, this study formulates three ethical principles for environmental use: proportionality, accountability, and intergenerational sustainability. The study concludes that taskhīr is not a license for exploitation but a trust that obliges humans to preserve nature for future generations.